Antimicrobial compounds from marine Actinomycetes - Wang, Cong (Arch Pharm Res, 2020)
Marine actinomycetes were the main origin of marine natural products in the past forty years. This review was to present the sources, structures and antimicrobial activities of 313 new natural products from marine actinomycetes reported from 1976 to 2019.